Sama celebrations ritual, music and dance of Sama Dilaut and Sama Bajau in Southern Philippines and North Borneo - Hanafi Hussin; Santamaria, M. C. M. (Monograph series (Universiti Malaya. Institute of Ocean and Earth Sciences), 2013)
Sama identity, as the chapters in this volume indicate, is University of Malaya closely linked with artistic expressions. It appears that among the most salient of these expressions in terms of creating and transmitting identity are music and dance. Along with other elements of ritual in which they are embedded, these traditional forms constitute veritable sources of collective memory, conceptions of their cosmos, and are by way of practice and belief considered to be indispensable media for encounters with the spirit world, most importantly their omboh or ancestors who are believed to be constantly looking over their welfare.